Association of Waist-Hip Ratio with Angiographic Severity of Coronary Artery Disease in Patients with Acute ST- Segment Elevation Myocardial Infarction - Hossain, Mohammad Anowar; Akanda, Md Abdul Kader; Ullah, Mohammad; Barai, Lakshman Chandra; Uddin, ABM Nizam; Huda, Reaz Mahmud; Hossain, Muhammad Azmol; Haque, Md Mosharul; Islam, Abul Khair Md Rezawanul; Siddiqui, Mohammad Khalilur Rahman (Bangladesh Heart Journal, 2018)
Objective: Coronary artery disease (CAD) is rising in South Asia and is taking a more malignant proportion in South Asians than in Caucasians. Having a similar socioeconomic and cultural background, the scenario is same in Bangladesh. Obesity, especially abdominal is concerned as an important and modifiable risk factor for CAD which is now also raising both in developed and under developed countries. Waist-Hip ratio (WHR) is considered as an important tool for assessing abdominal obesity. The aim of this study is to evaluate the association between WHR and the severity of CAD of acute ST-segment elevation myocardial infarction (STEMI) patients so that primary prevention, early detection and proper management strategy can be taken to reduce the disease burden, morbidity and mortality. Methods: This cross sectional observational study was carried out among 105 patients with acute STEMI who received thrombolytic and underwent coronary angiography (CAG) at National Institute of Cardiovascular Diseases (NICVD), Dhaka from May, 2016 to November, 2016. They were divided into two groups, Group I (normal WHR) = 51 and group II (increased WHR) = 54, according to WHR level. Angiographic severity of coronary artery disease was assessed by vessel score and Genseni’s score. Results: Significant positive correlation was found between WHR and vessel score (r= 0.62, p=0.003). Moderate to severe CAD patients were significantly higher in increased WHR group than in normal WHR group (77.8% vs. 29.4%, p=<0.001). Significant positive correlation was also found between WHR and Genseni’s score (r= 0.71, p=0.001). Logistic regression analysis showed that a patient with increased WHR had 2.75 times higher risk of having significant CAD compared with those with the normal WHR. Conclusions: Increased WHR group had more significant coronary artery disease in terms of vessel score and Genseni’s score and can be considered as a predictor of the severity of the CAD disease in acute STEMI patients. Bangladesh Heart Journal 2017; 32(2) : 70-76